Learning Module Based Problem-Based Learning Local Wisdom Lubuk Larangan to Improve Critical Thinking and Learning Interest of Students - Meridayati Nasution; Lufri Lufri; Fitri Arsih; Rahmawati D (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
Biology learning at the senior high school level often involves complex material that requires not only deep understanding but also high motivation. Observations at SMAN 3 Panyabungan revealed that students demonstrated low levels of critical thinking and interest in learning, as the teaching approach primarily relied on textbooks and worksheets without incorporating engaging or contextual media. To address this issue, a Biology Learning Module based on Problem-Based Learning (PBL) was developed, integrating the local wisdom of Lubuk Larangan. This study employed a Research and Development (R&D) approach, utilizing the ADDIE model, which comprises analysis, design, development, implementation, and evaluation stages. The research subjects were Grade X Phase E students of SMAN 3 Panyabungan in the 2024/2025 academic year. Data were collected using validity questionnaires, practicality questionnaires, motivation questionnaires, and test instruments. The developed module achieved a validity score of 95.6% (very valid) and a practicality score of 4.0 (very practical). In terms of effectiveness, the module significantly improved students’ critical thinking skills and increased their learning interest, with an average percentage of 73.2% (classified as good). The Biology Learning Module, based on Problem-Based Learning (PBL) and integrated with Lubuk Larangan local wisdom, is valid, practical, and effective in improving students’ motivation, learning interest, and argumentation skills, particularly in ecosystem-related topics.